Medical Professionals and Pharmacological Intervention for the Treatment of Insomnia: A Cross-Sectional Study - Antonios Liaskopoulos; Vasileios Kakouris; Nikolaos Liaskopoulos; Andreas S. Lappas; Nikolaos Christodoulou; Myrto Samara (Sleep Science)
Objective To explore the preferences of medical practitioners concerning various medications and other remedies to manage insomnia, and to ascertain whether these preferences are associated with their respective medical specialties.